Lithium battery organic-inorganic composite flame-retardant diaphragm and preparation method thereof

By adding a composite coating of benzoxazine resin particles and natural clay mineral nanotubes to the lithium-ion battery polyolefin separator, the problem of polyolefin separator is easily shrinkable and flammable under high temperature conditions, achieving higher thermal stability and flame retardant performance, and improving the thermal safety of the battery and the electrolyte liquid absorption rate.

CN119627364AInactive Publication Date: 2025-03-14ANHUI ZHONGKE RISHENG TECH CO LTD +1

Patent Information

Application Number
CN202411488615.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-ion battery polyolefin separators are prone to shrink and burn under high temperature conditions, and have poor affinity for electrolytes, which cannot meet the needs of high energy density and high power output.

Method used

The organic-inorganic composite flame retardant membrane is used, and the base membrane is made of polyolefin membrane, and the outer coating is made of benzoxazine resin particles, natural clay mineral nanotubes and additives. The mass ratio is 40% to 95%: 5% to 60%.

Benefits of technology

The thermal dimensional stability and flame retardant properties of the lithium battery separator are improved, the affinity for the electrolyte is enhanced, and the thermal safety of the battery cell is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627364A_ABST
    Figure CN119627364A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium battery organic-inorganic composite flame-retardant diaphragm which comprises a base material diaphragm and a flame-retardant layer on the outer side of the base material diaphragm, the base material diaphragm is a polyolefin diaphragm, and the flame-retardant layer is prepared from benzoxazine resin particles, natural clay mineral nanotubes and auxiliaries; the mass ratio of the benzoxazine resin particles to the natural clay mineral nanotubes is (40%-95%): (5%-60%). According to the present invention, the design is novel, the thermal stability and the flame retardant property of the polyolefin diaphragm in the lithium battery are effectively improved, the affinity of the polyolefin diaphragm to the electrolyte is improved, and the safety of the battery monomer is substantially improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to an organic-inorganic composite flame-retardant diaphragm for a lithium battery and a preparation method thereof. Background Art

[0002] With the development of the times and technology, people's demand for consumer electronics, power batteries and energy storage equipment is increasing. Lithium-ion batteries are widely used because of their high energy density and long cycle life. The diaphragm is one of the core materials of lithium-ion batteries. Its main function is to separate the positive and negative electrodes of the battery, ensuring the passage of lithium ions. It is a thin film with a microporous structure.

[0003] The performance of the separator determines the interface structure and internal resistance of the battery, and affects the battery capacity, cycle, etc. At present, polyolefin separators such as polypropylene separators (PP) and polyethylene separators (PE) are mainly used commercially. However, due to their thermal dimensional instability and poor affinity for electrolytes, they cannot meet the needs of high energy density and high power output.

[0004] The future development direction of lithium batteries is to improve safety and energy density. In actual applications, if the diaphragm melts and shrinks under abnormally high temperature conditions, causing a large-area short circuit in the battery, it will cause uncontrollable serious consequences and greatly affect the safety of lithium battery use. Summary of the invention

[0005] The purpose of the present invention is to solve the problems in the prior art that polyolefin separators of lithium ion batteries are easy to shrink and burn when heated and have poor affinity to electrolyte, and to propose an organic-inorganic composite flame retardant separator for lithium batteries.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A lithium battery organic-inorganic composite flame-retardant diaphragm, which is composed of a substrate diaphragm and a flame-retardant layer on its outer side, wherein the substrate diaphragm is a polyolefin diaphragm, and the flame-retardant layer is made of benzoxazine resin particles, natural clay mineral nanotubes and additives;

[0008] The mass ratio of the benzoxazine resin particles to the natural clay mineral nanotubes is 40% to 95%: 5% to 60%.

[0009] Preferably, the benzoxazine resin is at least one of bisphenol A type, bisphenol F type, phenol type, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide type, phenolphthalein type, bisphenol AF type, magnolol-furfurylamine type, cardanol-aniline type, dicyclopentadiene type, and diaminodiphenylmethane type;

[0010] The natural clay mineral nanotube is at least one of attapulgite nanotube and halloysite nanotube.

[0011] Preferably, the thickness of the substrate diaphragm is 5 to 35 μm;

[0012] The particle size of the benzoxazine resin particles is 0.05 to 5 μm;

[0013] The specific surface area of ​​the natural clay mineral nanotubes is 10 to 200 m2 / g.

[0014] Preferably, the auxiliary agent includes a dispersant, a wetting agent and a binder.

[0015] More preferably, the dispersant and wetting agent are at least one of fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium methylene bisnaphthalene sulfonate, polyether modified silicone, sodium aryl naphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium perfluorooctanoate, nonylphenol polyoxyethylene ether, sodium butyl naphthalene sulfonate, polyacrylate, polyethylene glycol, and sodium carboxymethyl cellulose;

[0016] The binder is at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium polyacrylate, and polyacrylonitrile multipolymer.

[0017] More preferably, it is characterized by a heat shrinkage rate of ≤5% at 180°C for 30 minutes, an air permeability of 105-483.6s / 100mL, an electrolyte absorption rate of 130.6-479.2%, and an ionic conductivity of 0.5-3.7mS / cm.

[0018] A method for preparing an organic-inorganic composite flame-retardant diaphragm for a lithium battery, characterized in that it comprises the following steps:

[0019] S10, mixing benzoxazine resin particles, natural clay mineral nanotubes, a dispersant, a wetting agent and water to obtain a mixed solution;

[0020] S20, adding an adhesive to the uniformly mixed solution, stirring and mixing to obtain a slurry.

[0021] S30, coating the slurry on the surface of the polyolefin diaphragm and drying to obtain a modified diaphragm.

[0022] Preferably, the step S10 specifically includes:

[0023] S101, mixing the benzoxazine resin particles, natural clay mineral nanotubes and water and performing ultrasonic dispersion treatment for 20 minutes to obtain a first intermediate solution;

[0024] S102, adding a dispersant and a wetting agent into the first intermediate solution and stirring for more than 6 hours to obtain the mixed solution.

[0025] More preferably, the mass ratio of the benzoxazine resin particles to the aqueous solvent is 2% to 40%;

[0026] The mass percentage concentration of the benzoxazine resin particles in the first intermediate solution is 1 to 60%, and the mass percentage concentration of the natural clay mineral nanotubes is 1 to 40%;

[0027] The mass percentage concentration of the dispersant in the mixed solution is 0.01-15%, and the mass percentage concentration of the wetting agent is 0.01-15%.

[0028] Preferably, the step S30 is specifically as follows:

[0029] The wet composite film is placed at room temperature for drying for 30 minutes, and then transferred to a blast oven for drying to obtain the organic-inorganic composite flame-retardant diaphragm for a lithium battery;

[0030] The drying temperature of the blast oven is set to 80° C., and the blast oven is dried for 5 to 15 minutes.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The composite flame-retardant diaphragm prepared by the present invention has excellent performance, good thermal dimensional stability and excellent flame retardant performance, and can be applied to lithium batteries to greatly improve the thermal safety of battery cells;

[0033] 2. The surface coating of the composite flame-retardant diaphragm prepared by the present invention has abundant channels and pores, and has high affinity for electrolyte, which greatly increases the electrolyte absorption rate of the composite diaphragm, is beneficial to the migration of lithium ions, and ensures the good performance of the battery monomer;

[0034] 3. The slurry used in the preparation of the composite flame-retardant diaphragm in the present invention is an environmentally friendly water-based slurry, which is simple to operate and has good compatibility. In addition, the raw materials used are in abundant reserves, and the industrial production conditions are perfect, which is convenient for controlling costs.

[0035] The invention has a novel design, effectively improves the thermal stability and flame retardancy of the polyolefin separator in the lithium battery, and enhances the affinity of the polyolefin separator to the electrolyte, thereby greatly improving the safety of the battery monomer. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The present invention is a flow chart of the method for preparing the organic-inorganic composite flame retardant diaphragm.

[0037] Figure 2 This is the SEM image of Celgard's 10um PE separator.

[0038] Figure 3This is a SEM image of the surface of the PE composite flame-retardant diaphragm prepared in Example 2 of the present invention.

[0039] Figure 4 These are actual photos of the PE diaphragm before and after heating at 180°C and the PE composite flame-retardant diaphragm prepared in Example 1.

[0040] Figure 5 These are photos of the PE diaphragm and the PE composite flame-retardant diaphragm prepared in Example 1 before and after ignition. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0042] Reference Figure 1-5 , a lithium battery organic-inorganic composite flame-retardant diaphragm, composed of a substrate diaphragm and a flame-retardant layer on its outer side, wherein the substrate diaphragm is a polyolefin diaphragm, and the flame-retardant layer is made of benzoxazine resin particles, natural clay mineral nanotubes and additives; wherein the mass ratio of benzoxazine resin particles to natural clay mineral nanotubes is 40% to 95%: 5% to 60%; under 180°C, the composite flame-retardant diaphragm has a 30min heat shrinkage rate of ≤5%, an air permeability of 105 to 483.6s / 100mL, an electrolyte absorption rate of 130.6 to 479.2%, and an ionic conductivity of 0.5 to 3.7mS / cm. The composite diaphragm has a high affinity for electrolyte, greatly increases the electrolyte absorption rate of the composite diaphragm, and is beneficial to the migration of lithium ions.

[0043] The benzoxazine resin is at least one of bisphenol A type, bisphenol F type, phenol type, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide type, phenolphthalein type, bisphenol AF type, magnolol-furfurylamine type, cardanol-aniline type, dicyclopentadiene type, and diaminodiphenylmethane type; the natural clay mineral nanotube is at least one of attapulgite nanotube and halloysite nanotube.

[0044] The thickness of the substrate membrane is 5 to 35 μm; the particle size of the benzoxazine resin particles is 0.05 to 5 μm; and the specific surface area of ​​the natural clay mineral nanotubes is 10 to 200 m2 / g.

[0045] The auxiliary agent includes a dispersant, a wetting agent and a binder; the dispersant and the wetting agent are at least one of fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium methylene bisnaphthalene sulfonate, polyether modified silicone, sodium aryl naphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium perfluorooctanoate, nonylphenol polyoxyethylene ether, sodium butylnaphthalene sulfonate, polyacrylate, polyethylene glycol, and sodium carboxymethyl cellulose; the binder is at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium polyacrylate, and polyacrylonitrile multipolymer.

[0046] The preparation method of the composite flame-retardant diaphragm of the present invention is as follows: the synthesized benzoxazine microparticles and natural clay mineral nanotubes are dispersed in an aqueous solution, a dispersant, a wetting agent and a binder are added to prepare an aqueous environmentally friendly slurry; the slurry is coated on a polyolefin diaphragm to form a uniform coating. Due to its high glass transition temperature and the fact that it is a thermosetting resin, the benzoxazine resin microparticles can improve the heat resistance of the lithium-ion battery diaphragm, and synergize with the natural clay mineral nanotubes to give the composite diaphragm a flame-retardant function, which can self-extinguish after ignition, thereby comprehensively improving the thermal safety of the battery cell.

[0047] The following is a specific embodiment according to this preparation method:

[0048] Embodiment 1

[0049] In this embodiment, bisphenol A is used as the benzoxazine resin; the dispersant, wetting agent and adhesive are all purchased from BYK Chemical, and the specific brands are as follows: the dispersant is an ammonium acrylate dispersant, BYK-LPC20992; the wetting agent is a silicone surfactant wetting agent, BYK-LPX20990; the adhesive is a polyacrylate adhesive, BYK-LPC22346; the diaphragm substrate is a commercial polyolefin diaphragm, specifically, a 10μm thick PE diaphragm from Celgard.

[0050] The raw materials are preliminarily processed before preparing the composite flame retardant diaphragm:

[0051] Preparation of benzoxazine resin microparticles:

[0052] The solid powder of the benzoxazine resin was placed in a muffle furnace to be fully cured. The solidified benzoxazine resin was taken out, and the solid was properly crushed with a pestle, and then put into a universal grinder, the speed was set to 12000 rpm, and the cumulative crushing was 30 minutes to obtain benzoxazine resin powder.

[0053] Substrate diaphragm treatment:

[0054] The PE diaphragm does not require any special treatment before coating, just ensure that the diaphragm surface is clean.

[0055] The specific preparation method of the composite flame retardant diaphragm is as follows:

[0056] Step 1: Prepare a modified benzoxazine resin submicron particle suspension, mix the benzoxazine resin microparticles with deionized water, add them to a vertical ball mill at a solid-liquid mass ratio of 1 to 10, control the speed at 120 to 180 rpm, and process for 96 hours. The milled slurry is directly processed in a nano sand mill for the final machining, and the speed is controlled at 1800 rpm for 12 hours to obtain a modified benzoxazine resin submicron particle suspension. The diameter of the prepared modified benzoxazine resin microparticles is controlled at 400 to 1500 nm.

[0057] Step 2: Prepare flame-retardant membrane coating slurry, take 90 parts by mass of benzoxazine resin and 10 parts by mass of halloysite nanotubes, and prepare a suspension with a solid content of 11%. Then add 2% by mass fraction of BYK-LPC20992 and 1% BYK-LPX20990 wetting agent, transfer to a magnetic stirrer and stir for 24 hours, after mixing evenly (the mixed solution is left to stand for half an hour without obvious precipitation), add 5% of acrylate BYK-LPC22346 adhesive, continue stirring for 6 hours, and obtain an aqueous coating slurry of benzoxazine resin particles and halloysite nanotubes.

[0058] Step 3: Slurry coating: Use an automatic coating machine to evenly coat the slurry on the PE diaphragm to obtain a composite wet film, place it at room temperature for 30 minutes (taking 25°C as an example), and after there is no water mark on the surface of the composite diaphragm, transfer it to an 80°C forced air oven for vacuum drying for 10 minutes to obtain a BEN-HNTs@PE diaphragm coated with benzoxazine particles and halloysite nanotubes on one side. Repeat the above steps to coat the other side, and obtain a PE composite diaphragm coated with flame retardant materials on both sides (hereinafter referred to as BEN-HNTs@PE diaphragm).

[0059] Embodiment 2

[0060] The method is basically the same as Example 1, except that, in the preparation step 2, 70 parts of benzoxazine resin and 30 parts of halloysite nanotubes are selected.

[0061] Embodiment 3

[0062] The method is basically the same as Example 1, except that, in the preparation step 2, 55 parts of benzoxazine resin and 45 parts of halloysite nanotubes are selected.

[0063] Embodiment 4

[0064] The method is basically the same as Example 1, except that in the preparation step 2, 40 parts of benzoxazine resin and 60 parts of halloysite nanotubes are selected.

[0065] Comparative Example

[0066] Without the above treatment, unmodified clean PE diaphragm is selected.

[0067] Evaluation Method

[0068] The BEN-HNTs@PE separator prepared above was subjected to performance tests, including air permeability, weight, thickness, surface density, liquid absorption rate, micromorphology, ionic conductivity, thermal dimensional stability and flame retardancy.

[0069] The specific performance test methods are as follows:

[0070] 1. Air permeability test: Use the American Gurley 4110N air permeability tester to test the air permeability of the diaphragm. The air permeability of the diaphragm reflects the tortuosity of the internal pores of the diaphragm and the true path of ion diffusion. It is proportional to the ion conductivity and can be evaluated by the Gurley value. The Gurley value refers to the time required for a certain amount of air to pass through a unit area of ​​the diaphragm under a certain specified pressure, in seconds.

[0071] 2. Surface density test: The surface density of the BEN-HNTs@PE diaphragm was calculated by slicing and weighing. The diaphragm was cut into 16.5 mm diameter discs using a slicer. The discs were weighed one by one and the average value was calculated.

[0072] 3. Thickness test: Use a handheld thickness gauge to test the thickness of the BEN-HNTs@PE diaphragm.

[0073] 4. Liquid absorption rate test: Use the weighing method to test the liquid absorption rate of the diaphragm, that is, calculate the liquid absorption rate of the diaphragm by the change in weight before and after the diaphragm absorbs liquid: weigh a disc membrane with a diameter of 16.5 mm, and then immerse it in a liquid electrolyte of EC:DMC (3:7, v / v, containing 1.0 mol / L LiPF6) for 1 hour. After taking it out, gently wipe off the surface liquid with filter paper, weigh it, and calculate the liquid absorption rate EU. The calculation formula is:

[0074] EU(%)=(W2-W1) / W1×100%

[0075] Among them, W1 and W2 are the mass (g) of the diaphragm before and after wetting in the electrolyte.

[0076] 5. Detection of diaphragm surface morphology: Use a cold field scanning electron microscope to observe the surface morphology of the flame retardant diaphragm.

[0077] 6. Ionic conductivity test: The bulk impedance of the BEN-HNTs@PE diaphragm was tested on an electrochemical workstation (Bio-Logic VSP-300) by electrochemical impedance spectroscopy (EIS), and its ionic conductivity was obtained. A stainless steel symmetrical cell was assembled for testing. The frequency range was 106 to 10-1 Hz, and the AC amplitude was 10 mV. The ionic conductivity calculation formula is as follows:

[0078] σ=D / RS

[0079] Wherein, σ represents the ionic conductivity of the membrane; D represents the thickness of the membrane; R is the horizontal intercept of the Nyquist plot; and S represents the area of ​​the membrane.

[0080] 7. Thermal dimensional stability test: Observe the dimensional changes of the BEN-HNTs@PE diaphragm before and after heating at 180°C for 30 minutes.

[0081] 8. Flame retardant performance test: Use a cutting machine to cut the diaphragm into discs with a diameter of 16.5 mm, burn the diaphragm over the flame of an alcohol lamp, remove the flame range after staining, and record the burning phenomenon with a digital camera.

[0082] The above test results are statistically analyzed and recorded in Table 1.

[0083] Table 1. Composite flame retardant diaphragm performance test data

[0084]

[0085]

[0086] Combined with the data in Table 1, the BEN-HNTs@PE diaphragm prepared in the present application has excellent performance, good thermal dimensional stability, and outstanding flame retardant properties; in addition, the composite diaphragm coating contains abundant channels and pores, has high affinity for the electrolyte, greatly increases the composite diaphragm's absorption rate for the electrolyte, and is beneficial to the migration of lithium ions.

[0087] Through Figure 2 and Figure 3 Observation of the SEM image of the diaphragm surface, Figure 2 The surface of the commercial PE separator shows a large number of evenly distributed pores; Figure 3 In the BEN-HNTs@PE separator prepared by the scheme in Example 1, the benzoxazine resin particles and halloysite nanotubes on its surface are staggered, and the ball-and-stick coating formed by them evenly covers the base film, indicating that the slurry formula has good coatability for polyolefin separators. In addition, the large number of pores between the ball-and-stick coatings can also absorb electrolytes, providing abundant channels for the transmission of lithium ions.

[0088] Combination Figure 4 From the comparison of the heating experiments at 180°C on the diaphragms, it can be seen that the commercial PE diaphragm obviously shrinks, melts and then solidifies, changing from a round shape to a tiny light white plastic mass, while the BEN-HNTs@PE diaphragm prepared in Example 1 shows basically no obvious shrinkage after heating. It can be seen that the composite flame-retardant diaphragm prepared in this application has very excellent thermal dimensional stability.

[0089] Combined with Table 1 Figure 5 From the comparison of the burning experiments on the diaphragms, it can be seen that the PE diaphragm shrinks rapidly into a ball the moment it contacts the flame, and then burns out; while the BEN-HNTs@PE diaphragm does not shrink significantly when it contacts the flame and can maintain its basic shape. After leaving the flame, the burning part begins to carbonize, and then the burning flame becomes smaller until it goes out. Thanks to the synergistic effect of the inorganic flame retardant material and the organic thermosetting particles, a protective layer with a dense structure is formed on the surface and inside of the coating, which effectively isolates oxygen and inhibits further combustion of the base film, thereby exhibiting excellent flame retardancy.

[0090] Obviously, the PE composite flame-retardant diaphragm in the present application has excellent properties of high temperature resistance, flame retardancy, and high electrolyte absorption rate, and its use in batteries can greatly improve the thermal safety of battery cells.

[0091] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A lithium battery organic-inorganic composite flame retardant diaphragm, characterized in that: It is composed of a substrate diaphragm and a flame retardant layer on its outer side, wherein the substrate diaphragm is a polyolefin diaphragm, and the flame retardant layer is made of benzoxazine resin particles, natural clay mineral nanotubes and additives; The mass ratio of the benzoxazine resin particles to the natural clay mineral nanotubes is 40% to 95%: 5% to 60%.

2. The organic-inorganic composite flame-retardant diaphragm for lithium battery according to claim 1, characterized in that: The benzoxazine resin is at least one of bisphenol A type, bisphenol F type, phenol type, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide type, phenolphthalein type, bisphenol AF type, magnolol-furfurylamine type, cardanol-aniline type, dicyclopentadiene type, and diaminodiphenylmethane type; The natural clay mineral nanotube is at least one of attapulgite nanotube and halloysite nanotube.

3. The organic-inorganic composite flame-retardant diaphragm for lithium battery according to claim 1, characterized in that: The thickness of the substrate diaphragm is 5 to 35 μm; The particle size of the benzoxazine resin particles is 0.05 to 5 μm; The specific surface area of ​​the natural clay mineral nanotubes is 10 to 200 m 2 / g.

4. The organic-inorganic composite flame-retardant diaphragm for lithium battery according to claim 1, characterized in that: The auxiliary agents include dispersants, wetting agents and binders.

5. The organic-inorganic composite flame-retardant separator for lithium batteries according to claim 4, characterized in that: The dispersant and wetting agent are at least one of fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium methylene bisnaphthalene sulfonate, polyether modified silicone, sodium aryl naphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium perfluorooctanoate, nonylphenol polyoxyethylene ether, sodium butyl naphthalene sulfonate, polyacrylate, polyethylene glycol, and sodium carboxymethyl cellulose; The binder is at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium polyacrylate, and polyacrylonitrile multipolymer.

6. The organic-inorganic composite flame-retardant separator for lithium batteries according to any one of claims 1 to 5, characterized in that: The thermal shrinkage rate is ≤5% for 30 minutes at 180°C, the air permeability is 105-483.6s / 100mL, the electrolyte absorption rate is 130.6-479.2%, and the ion conductivity is 0.5-3.7mS / cm.

7. A method for preparing an organic-inorganic composite flame-retardant separator for a lithium battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: S10, mixing benzoxazine resin particles, natural clay mineral nanotubes, a dispersant, a wetting agent and water to obtain a mixed solution; S20, adding an adhesive to the uniformly mixed solution, stirring and mixing to obtain a slurry; S30, coating the slurry on the surface of the polyolefin diaphragm and drying to obtain a modified diaphragm.

8. The method for preparing an organic-inorganic composite flame-retardant diaphragm for a lithium battery according to claim 7, characterized in that: The step S10 specifically includes: S101, mixing the benzoxazine resin particles, natural clay mineral nanotubes and water and performing ultrasonic dispersion treatment for 20 minutes to obtain a first intermediate solution; S102, adding a dispersant and a wetting agent into the first intermediate solution and stirring for more than 6 hours to obtain the mixed solution.

9. The method for preparing an organic-inorganic composite flame-retardant diaphragm for a lithium battery according to claim 8, characterized in that: The mass ratio of the benzoxazine resin particles to the water solvent is 2% to 40%; The mass percentage concentration of the benzoxazine resin particles in the first intermediate solution is 1 to 60%, and the mass percentage concentration of the natural clay mineral nanotubes is 1 to 40%; The mass percentage concentration of the dispersant in the mixed solution is 0.01-15%, and the mass percentage concentration of the wetting agent is 0.01-15%.

10. The method for preparing an organic-inorganic composite flame-retardant diaphragm for a lithium battery according to claim 7, characterized in that: The S30 step is specifically as follows: The wet composite film is placed at room temperature for drying for 30 minutes, and then transferred to a blast oven for drying to obtain the organic-inorganic composite flame-retardant separator for lithium batteries; The drying temperature of the blast oven is set to 80° C., and the blast oven is dried for 5 to 15 minutes.

Citation Information

Patent Citations

  • Flame-retardant modified carbon fiber prepreg and composite material product

    CN104553177A

  • Polypropylene battery diaphragm containing composite coating and preparation method of polypropylene battery diaphragm

    CN105098120A

  • Flame-retardant lithium battery coating diaphragm, preparation method thereof and lithium ion battery

    CN116231228A

  • Coating composition, composite isolating membrane, battery monomer, battery and electric equipment

    CN116404361A

Cited By

  • Diaphragm, diaphragm coating and application

    CN121064693A

  • Coating slurry for lithium battery diaphragm, lithium battery diaphragm, preparation method of lithium battery diaphragm, lithium battery and electric equipment

    CN121983747A